Primary prophylaxis with pegfilgrastim in patients with newly-diagnosed diffuse large B-cell lymphoma: propensity score and instrumental variable analyses. Issue 10 (23rd August 2020) - Matsuda, Kensuke; Taisuke, Jo; Miyauchi, Masashi; Toyama, Kazuhiro; Nakazaki, Kumi; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo; Kurokawa, Mineo
Abstract: The clinical impact of pegfilgrastim in day-to-day practice remains unclear. This study evaluated the effectiveness of pegfilgrastim compared with daily filgrastim in patients with DLBCL who received the first-cycle of R-CHOP treatment by using a Japanese national inpatient database. Patient characteristics were adjusted by using propensity-score matching and stabilized inverse probability of treatment weighting (IPTW). In 1295 propensity-score-matched pairs, the incidence of febrile neutropenia was significantly lower in the pegfilgrastim group (risk difference 6.1%, 95% CI 4.1%–8.1%) than in the filgrastim group. In the pegfilgrastim group, the length of hospital stay and the total costs were also significantly reduced (percent reduction 34% [95% CI: 31%–37%], percent reduction 12% [95% CI: 9%–15%], respectively). The stabilized IPTW showed comparable results. In day-to-day practice, the simple mode of pegfilgrastim administration may be advantageous.